"Your Exile is Showing": Integrating Sandtray with Internal Family Systems Therapy. Issue 1 (18th November 2020) - Turns, Brie; Springer, Paul; Eddy, Brandon P.; Sibley, D. Scott
Abstract: Internal family systems (IFS) therapy is an experiential model of therapy and views individuals as having numerous "parts" inside of them. These parts maintain a specific role in a client's life and fall under one of the three categories – managers, exiles, and firefighters. Due to the experiential aspect of IFS and the concept of blending, visualizing the parts inside of a client can become challenging at best and impossible, at worst. This article provides a framework for integrating sandtray therapy with IFS to help clients name, visualize, and see the progress of their parts.